Tetramethylpyrazine inhibits CoCl2‐induced neurotoxicity through enhancement of Nrf2/GCLc/GSH and suppression of HIF1α/NOX2/ROS pathways. (3rd June 2015) - Guan, Dongsheng; Su, Yufei; Li, Yingxia; Wu, Chuanjie; Meng, Yi; Peng, Xin; Cui, Yinglin
Abstract Hypoxia‐mediated neurotoxicity contributes to various neurodegenerative disorders, including Alzheimer's disease and multiple sclerosis. Tetramethylpyrazine (TMP), a major bioactive component purified from Ligusticum wallichii Franchat, exhibited potent neuroprotective effect. However, the mechanism of TMP‐exerted neuroprotective effect against hypoxia was not clear. In the study, we investigated the mechanism of the neuroprotective effect of TMP against hypoxia induced by CoCl2in vitro and in vivo. The results showed that TMP could protect against CoCl2‐induced neurotoxicity in PC12 cells and in rats, as evidenced by enhancement of cell viability in PC12 cells and improvement of learning and memory ability in rats treated with CoCl2. TMP could inhibit mitochondrial dysfunction, mitochondrial apoptotic molecular events, and thus apoptosis induced by CoCl2. TMP inhibited CoCl2‐increased reactive oxygen species (ROS) level, which may contribute to hypoxia‐related neurotoxicity induced by CoCl2. The antioxidant and neuroprotective activities of TMP involved two pathways: one was the enhancement of nuclear factor erythroid 2‐related factor 2 (Nrf2)/catalytic subunit of γ‐glutamylcysteine ligase‐mediated regulation of GSH and the other was the inhibition of hypoxia‐inducible factor 1 α/NADPH oxidase 2 (NOX2)‐mediated ROS generation. These two pathways contributed to improvement of oxidative stress and thus the amelioration of apoptosis under hypoxic conditions. These results have appointed a new path toward the understanding of pathogenesis and TMP‐related therapy of hypoxia‐related neurodegenerative diseases. We proposed two cascades for tetramethylpyrazine‐exhibited protective effects against CoCl2‐induced neurotoxicity: One is enhancement of nuclear factor erythroid 2‐related factor 2‐catalytic subunit of γ‐glutamylcysteine ligase‐mediated regulation of glutathone and the other was the inhibition of hypoxia‐inducible factor 1 α‐NADPH oxidase‐2‐mediated ROS generation. We think these findings should provide a new understanding of pathogenesis and tetramethylpyrazine‐related therapy of hypoxia‐related neurodegenerative diseases.